Consumer Behavior toward Digital Transactions Using QRIS: A Technology Acceptance Model (TAM) Approach - R. Suprono Wahyujatmiko (PT. Anagata Sembagi Education, 2025)
This study aims to analyze consumer behavior toward digital transactions using the Quick Response Code Indonesian Standard (QRIS) through the Technology Acceptance Model (TAM) framework. A quantitative descriptive approach was applied to examine the relationships among perceived usefulness (PU), perceived ease of use (PEOU), attitude toward use (ATU), and behavioral intention (BI) in determining consumer acceptance of QRIS. Data were collected from active users of digital payment systems in Indonesia and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings reveal that perceived usefulness and perceived ease of use significantly influence users’ positive attitudes toward QRIS, which subsequently enhance their behavioral intention to use. Trust and perceived security also play crucial roles in reinforcing the relationship between attitude and intention. Theoretically, this research confirms the robustness of the TAM framework within the context of financial technology adoption in developing economies. Practically, the study provides strategic implications for monetary authorities and digital payment providers to increase QRIS adoption through user experience enhancement, digital literacy programs, and stronger regulatory measures for transaction security.